Enhancing the Quality of Learning through an E-Learning-Based Academic Management Information System at Madrasah Aliyah Negeri - Sudrajat, Jajat; Mayasari, Annisa; Arifudin, Opan (LP. Ma'arif Janggan Magetan, 2024)
The motivation for this research stems from the significant impact of information technology on education, ushering in a new era of development. However, this technological advancement has not been accompanied by a proportional increase in human resources, creating a need for systemic changes to expedite improvements and achieve quality education objectives. This study aims to analyze the planning, organization, implementation, supervision, and influencing factors (both supportive and detrimental) of an e-learning-based academic management information system, as well as its impact on enhancing learning quality at MAN 1 Bandung. Utilizing a qualitative methodology, the research findings indicate that the e-learning-based Academic Management Information System positively affects learning quality through engaging slide presentations and effective teaching methods, enabling both teachers and students to participate in a serious yet enjoyable learning process. the result shows that the implementation of e-learning in Islamic Religious Education can significantly enrich students' learning experiences and facilitate wider access to teaching materials. The conclusion is that effective implementation of e-learning platforms, coupled with strategic management and quality control, is crucial for optimizing educational outcomes and fostering a dynamic learning environment.